Relationship between entrepreneurial orientation, marketing capability and business performance in retail supermarkets in Santa Catarina (Brazil) - Ismael Luiz dos Santos; Sidnei Vieira Marinho (Innovation & Management Review, 2018)
Purpose: This study aims to find evidence of a possible relationship between three constructs that are generally investigated separately: entrepreneurial orientation, understood as entrepreneurship on the organizational level; marketing capability, seen as a highly competitive factor for the organization; and business performance, highlighted as a focus of the entire organization. Design/methodology/approach: A survey-based quantitative approach was adopted with a cross-sectional temporal perspective. To arrive at results that can be compared, the study uses factor analysis and structural equations modeling techniques, with estimations of maximum likelihood for testing the quality of fit of the measures to the structural models, using SPSS 21 and AMOS 16 software. Data were collected at the 27th EXPOSUPER, which is a trade fair at which 35,000 visitors were present. The data collection instrument used is a questionnaire previously validated by Reis Neto et al. (2013a). The first section covers control variables chosen to profile the firms, the second contains entrepreneurial orientation variables, the third comprises marketing capability variables and the fourth section contains business performance variables, all using seven-point Likert response scales. Findings: Tests of the entrepreneurial orientation measurement scale produced interesting results in this application within the retail supermarket industry. The results of exploratory factor analysis indicated that a scale with three dimensions was significant. The relationship between entrepreneurial orientation and marketing capability (H1) is positive, through the intermediate dimensions of innovation, proactiveness and risk-taking, used by firms' management, contributing to their efforts to research and manage the market, to develop products and services and to offer better prices. Exploratory factor analysis and confirmatory factor analysis showed that four of the scale's dimensions of the marketing capability were significant: market research, market management, new product development and pricing. Comparison of these results with those of Reis Neto et al. (2013a) reveals a difference, as although their result, achieved using structural equations modeling, also had four factors; the promotion dimension was the most significant and absorbed the other variables. Despite these differences, confirmatory factor analysis and structural equations modeling demonstrated that this construct met the minimum conditions for adequacy, where (H2), formulated to test the relationship between the marketing capability construct, was confirmed. The final construct analyzed in this study was business performance, initially suggested by González-Benito et al. (2009), and also used by Reis Neto et al. (2013a). They used the dimensions profitability, market value and market response, and in the present study, after exploratory factor analysis, confirmatory factor analysis and structural equations modeling, the results were identical to those authors results, in that (H3), formulated with the objective of testing the relationship between the entrepreneurial orientation construct and business performance, was confirmed, and although this was not the most robust of the relationships postulated in the three hypotheses, but was of lower significance. Research limitations/implications: Although this study has achieved its objective, one of the study's limitations relates to the data collection instrument, which was subject to failures in terms of the number of variables to be analyzed in each dimension. This led to elimination of certain dimensions during the analyses. Another limitation is related to the method used in the study. When questionnaires are used as data collection instruments, respondents often may not understand the true meaning of questions, which could lead them to choose any option, thereby stripping the results of credibility. In view of this limitation, it is suggested that future researchers conduct qualitative studies, using the case study method, which could offer greater clarity and increase understanding of the results related to these subjects. Even considering that this study has certain limitations and restrictions affecting generalization, it is hoped that it raises new questions, interests and inspirations, improving and complementing understanding of this strong social and economic sector. Originality/value: It is identify the relationship between entrepreneurial orientation and marketing capability, since to date there is no evidence from studies confirming the existence of such a relationship. This statement was based on the results of a bibliographic survey conducted using the ProKnow-C, knowledge development process-constructivist methodology, in which, this originality was positive and significant, offering new studies from this point of view.
Keywords: 650; Entrepreneurial orientation; Marketing capability; Business performance